2021
DOI: 10.12669/pjms.37.5.4135
|View full text |Cite
|
Sign up to set email alerts
|

Study on the correlation between Left Ventricular Hypertrophy and Coronary Artery disease in the very elderly patients with hypertension

Abstract: Objective: To investigate the relationship between left ventricular hypertrophy (LVH) and coronary artery disease in the very elderly (over 80 years old) patients with hypertension. Methods: One hundred twenty cases of very elderly patients with hypertension admitted to our hospital from March 2018 to December 2020 were selected and divided into two groups: the LVH group and the non-LVH group, all of whom were older aged over 80 years, including 62 patients in the LVH group and 58 patients in the non-LVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A similar study showed that the various dyslipidemias are significantly correlated with multi-vessel CAD ( 21 ). Left ventricular hypertrophy is also documented to predict multi-vessel CAD and heart failure is obviously a mirror image of multiple territory involvement ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that the various dyslipidemias are significantly correlated with multi-vessel CAD ( 21 ). Left ventricular hypertrophy is also documented to predict multi-vessel CAD and heart failure is obviously a mirror image of multiple territory involvement ( 22 ).…”
Section: Discussionmentioning
confidence: 99%